Accumulation of Hydrogen Peroxide in Barley Seeds – A Key Factor for Malt Quality?. (2nd October 2021) - Baldus, Matthias; Heukäufer, Florian; Großpietsch, Carla; Methner, Frank-Jürgen
Abstract: Hydrogen peroxide (H2 O2 ) is a reactive oxygen species that contributes to undesired oxidation of barley ingredients that are crucial for beer production and quality. H2 O2 reveals a dual role in plant physiology as it is involved in oxidative damage of biomolecules, but also actively synthesized for growth regulating processes. As H2 O2 formation in barley and its consequences for malt quality have not been investigated before, a method for H2 O2 quantification throughout malting is presented in this work to investigate this pathway's potential involvement in oxidative reactions in malt production. During germination, H2 O2 steadily accumulated in the barley seeds reaching concentrations up to approximately 2.5 µmol/g (dm). Barley variety, aeration rate, as well as water content during steeping were significant impact factors for H2 O2 formation. H2 O2 strongly correlated with the barley acrospire lengths indicating its beneficial involvement in growth regulation. During withering and kilning, the majority of H2 O2 was exponentially degraded. It is proposed that after its controlled synthesis during germination, H2 O2 acts as a primary oxidant of malt ingredients during withering and kilning. The barley metabolism-derived H2 O2 accumulation is discussed in relation to oxidative stability of malt, wort, and beer. The data of this work can be used as a fundament to control oxidative damage during malting.